AN OVERVIEW OF THE TRIPS AGREEMENT AND ITS IMPACT ON GLOBAL COPYRIGHT STANDARDS - Fayzullayeva Shaxlo Jumaniyoz qizi (Scholar Express Journals, 2025)
Trade-Related Aspects of Intellectual Property Rights (TRIPS) Agreement is a landmark document in international trade law, which placed consistent minimum standards of intellectual property protection on World Trade Organization (WTO) member countries. The current article examines the impact of the TRIPS Agreement on global copyright standards, determining its contribution to harmonizing copyright laws, its bolstering of enforcement mechanisms, and its influence on national legislation. By means of an examination of the success and failures of TRIPS within various jurisdictions, the article aims to provide an insight into how the agreement affects the dynamic between copyright protection and trade, especially in an era of growing digitalization.
Keywords: TRIPS Agreement; copyright law